Smartphone-based alert of community first responders: A multinational survey to characterise contemporary systems - Tore Marks; Bibiana Metelmann; Lorenzo Gamberini; Camilla Metelmann; Sebastian Schnaubelt; Federico Semeraro; Carolina Malta Hansen (Resuscitation Plus)
Aim: Several countries worldwide have implemented systems to alert community first responders (CFR) via smartphone applications to increase likelihood of survival after out-of-hospital cardiac arrest (OHCA). Substantial heterogeneity across CFR systems has been reported but recent reports are lacking. The European Resuscitation Council (ERC) conducted a survey to characterise and compare CFR systems focusing on requirements for joining CFR programs. Methods: An online survey with 28 questions regarding general system description, CFR qualification and training was conducted using SurveyMonkey between October 2024 and January 2025. The survey was shared via QR-code at the ERC Congress 2024, e-mail invitations to all ERC national resuscitation councils, the ERC Guidelines 2025 webpage, ERC social media, ERC newsletter, and personal e-mail invitations to research groups and CFR systems. Results: Thirty-five CFR systems from 19 countries participated in the survey. The majority of CFR systems (69%, n = 24) require some kind of Basic Life Support (BLS) training as a minimum qualification. In 80% (n = 28) the minimum age for participation is 18 years. App-specific training is offered by 51% (n = 18) and in 11% (n = 4) of CFR systems no dispatch centre is involved in the alert, 43% (n = 15) of systems alert exclusively to OHCA, and 17% (n = 6) of CFR systems only alert CFR to adult OHCAs. Conclusions: There are multiple CFR systems with a high degree of heterogeneity regarding minimum required CFR qualification and training as well as alerting modalities. Understanding these differences across systems is paramount to design studies to test the effect of CFR on patient outcomes.